Simplifying
x + 6 = 3x + -14
Reorder the terms:
6 + x = 3x + -14
Reorder the terms:
6 + x = -14 + 3x
Solving
6 + x = -14 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
6 + x + -3x = -14 + 3x + -3x
Combine like terms: x + -3x = -2x
6 + -2x = -14 + 3x + -3x
Combine like terms: 3x + -3x = 0
6 + -2x = -14 + 0
6 + -2x = -14
Add '-6' to each side of the equation.
6 + -6 + -2x = -14 + -6
Combine like terms: 6 + -6 = 0
0 + -2x = -14 + -6
-2x = -14 + -6
Combine like terms: -14 + -6 = -20
-2x = -20
Divide each side by '-2'.
x = 10
Simplifying
x = 10
Answer:
Thus, the value of expression is .
Step-by-step explanation:
Given : 3 + (2 + 8)power 2 ÷ 4 × 1 over 2 to the power of 4
Mathematically written as
We apply BODMAS,
Where ,
B stands for brackets
O stands for order
D stands for division
M stands for multiplication
A stand for addition
S stands for subtraction.
Consider the given expression,
Using BODMAS rule, solving for brackets first,
Thus, the value of expression is
Answer:
Step-by-step explanation:
The total number of workers is our unknown. If 40% of this unknown number are women and the number of women is 1380, then the equation looks like this:
(remember that the word "of" generally means to multiply)
(also remember that we have to use the decimal form of a percent in an equation)
.40(x) = 1380 then divide to get the number of total workers:
x = 3450